2004
DOI: 10.1007/s00277-004-0860-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results of tonsillar lymphoma: a 10-year experience

Abstract: Primary extranodal non-Hodgkin's lymphomas of the head and neck account for 10-20% of all non-Hodgkin's lymphomas. Primary tonsillar lymphoma accounts for less than 1% of head and neck malignancies, although the tonsil is the most common primary extranodal site of head and neck non-Hodgkin's lymphomas. In this study we analyzed our cases of tonsillar lymphoma treated in our institution during the last 10 years to compare the finding of this study with those of previous studies. We reviewed the cases of tonsill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 20 publications
0
21
0
6
Order By: Relevance
“…Furthermore, a majority of these patients (60%-70%) present with early stage (stages I and II) disease. 6,7 Gao et al 19 reported 69.6% of their patients to have localized (stage I or II) disease, whereas in the series by Mohammadianpanah et al 17 18% of patients had stage I and 67% had stage II disease. From January 1990 to December 2002, 148 patients with NHL involving the tonsil were treated at the Tata Memorial Hospital, Mumbai.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, a majority of these patients (60%-70%) present with early stage (stages I and II) disease. 6,7 Gao et al 19 reported 69.6% of their patients to have localized (stage I or II) disease, whereas in the series by Mohammadianpanah et al 17 18% of patients had stage I and 67% had stage II disease. From January 1990 to December 2002, 148 patients with NHL involving the tonsil were treated at the Tata Memorial Hospital, Mumbai.…”
Section: Discussionmentioning
confidence: 84%
“…Combined chemo radiation has been used as the primary treatment for localized aggressive non-Hodgkin's lymphoma [7] . However, a definite recommendation for treatment of primary ALK negative tonsillar lymphoma is difficult to make as larger studies are needed to throw light on the same [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Већина тонзиларних лимфома је пореклом B-ћелија и дифузни великоћелијски B-лимфом је најчешћи 67%-96%, следи MCL са 10%. Тонзиларни лимфоми имају добру прогнозу 5 . Већина ових пацијената има локализовану болест 6,7,8,9 , стадијум 1 или 2.…”
Section: уводunclassified